Bcl‐2‐negative IGH‐BCL2 translocation‐negative follicular lymphoma of the thyroid differs genetically and epigenetically from Bcl‐2‐positive IGH‐BCL2 translocation‐positive follicular lymphoma. Issue 4 (3rd August 2021) - Hamamoto, Yuichiro; Kukita, Yoji; Kitamura, Masanori; Kurashige, Masako; Masaie, Hiroaki; Fuji, Shigeo; Ishikawa, Jun; Honma, Keiichiro; Wakasa, Tomoko; Hanamoto, Hitoshi; Hirokawa, Mitsuyoshi; Suzuki, Ayana; et al.
Abstract : Aims: Follicular lymphoma (FL), comprising a minor subset of primary thyroid lymphomas, is divided into two groups based on Bcl‐2 expression and IGH‐BCL2 translocation. The clinicopathological features exhibited by Bcl‐2‐negative IGH‐BCL2 translocation‐negative FL of the thyroid (Bcl‐2 – / IGH‐BCL2 – tFL) are different from those of conventional FL; however, its lymphomagenesis remains unclear. Here, we collected samples from seven patients with Bcl‐2 – / IGH‐BCL2 – tFL to investigate their epigenetic and genetic aberrations. Methods and results: The immunohistochemical profiles of epigenetic modifiers and the methylation status of histones were examined, including EZH2, MLL2/KMT2D, CBP/CREBBP, EP300, H3K27me3 and H3K4me3, in Bcl‐2 – / IGH‐BCL2 – tFL and Bcl‐2‐positive IGH‐BCL2 translocation‐positive FL of the thyroid (Bcl‐2 + / IGH‐BCL2 + tFL). Most Bcl‐2 – / IGH‐BCL2 – tFLs retained the positivity of epigenetic modifiers and lower expression of H3K27me3, although Bcl‐2 + / IGH‐BCL2 + tFLs exhibited aberrant immunohistochemical patterns of EZH2 and CBP/CREBBP and overexpression of H3K27me3. Samples from seven cases were further analysed using targeted sequencing, focusing on the exons of 409 key tumour suppressor genes and oncogenes. Bcl‐2 – / IGH‐BCL2 – tFLs do not have pathogenic mutations of epigenetic modifiers, such as EZH2, MLL2/KMT2D, MLL3/KMT2C, EP300 and ARID1A, which have been reported in FLs in the literature, whereas Bcl‐2 + / IGH‐BCL2 + tFLs are probably pathogenic/pathogenic missense mutations or frameshift mutations of these genes. Additionally, novel mutations in TET2 and EP400 were detected in Bcl‐2 – / IGH‐BCL2 – tFLs. Conclusions: Different genetic and epigenetic abnormalities might be involved in the oncogenesis of Bcl‐2 – / IGH‐BCL2 – tFLs from Bcl‐2 + / IGH‐BCL2 + tFLs and other FLs. Abstract :